Let's solve the equation \(2(x + a) = 4b\) for the variable \(a\).
A. Solve the equation for \(a\):
-
Start with the given equation: \[ 2(x + a) = 4b \]
-
Divide both sides by 2 to simplify the equation: \[ x + a = \frac{4b}{2} \] \[ x + a = 2b \]
-
Isolate \(a\) by subtracting \(x\) from both sides: \[ a = 2b - x \]
Thus, the solution for \(a\) is: \[ \boxed{a = 2b - x} \]
B. Explanation of the process:
In solving for \(a\), I began with the equation \(2(x + a) = 4b\) and applied algebraic operations to isolate the variable \(a\). First, I divided both sides of the equation by 2 to eliminate the coefficient in front of the parentheses. This step simplified the equation and allowed me to express the sum \(x + a\) as \(2b\). Finally, to solve for \(a\), I rearranged the equation by subtracting \(x\) from both sides, which yielded the final expression \(a = 2b - x\).